Zasady oceny czasopism humanistycznych i ich rola w parametryzacji jednostek naukowych - Kulczycki, Emanuel (My University, 2014)
The article considers a problem of evaluating the humanities and a parametric evaluation of scientific journals. It concentrates on the three parts (A, B, C) of the list of scientific journals published by the Ministry of Science and Higher Education in Poland. In this article, I demon- strate a specific character of publishing practices in the humanities. The argument is divided into six sections. In the first one, I introduce the research problem and define the purpose of the article. In the second section, I distinguish two functions of the parametric evaluation of re- search (the declared and the unintentional one). In the third section, I show what is the diffe- rence between the citation culture in the science and in the humanities. Using these findings, I then present the rules of the list of scientific journals published by the Ministry of Science and Higher Education in this article in section four. The section number five provides suggestions and improvements for the construction rules of the scientific journals list. In the final section, I take into consideration the findings of the previous sections and show how they can be used for further evaluation of research in Poland.
Keywords: scientific journal; evaluation of science; Ministry of Science and Higher Education in Poland; humanities; Impact Factor